Deliceux Homemade Bread / Nurul Izzati Abdul Mutalib… [et al.] - Abdul Mutalib, Nurul Izzati; Baudin, Zainab; Mohd Fouzli, Puteri Fariha Awatif; Rosaidi, Nur Amalina (2012)
Firstly of all I would like to thanks to Allah SW.T because of His blessing, our job for ENT 300 or Fundamental Of Entrepreneurship assignment became smoothly and successful finished with have not any big problems. This report is about our knowledge on how we start to create our own business with our own effort, how we manage the business from the started until the end of the business and we learn about how to be alert to manage a successful business and also to compete with other businessman. Next, we want to say a lot of thanks to those who involve spending their time and contributed their ides to help us while doing this report. We’re really appreciated it. A big appreciation goes to our beloved lecturer, Madam Farhana. A lot of thanks to her because of her advices, then she willing to share with us the information for the ENT 300 report and she always guiding us along we do this job and the report. Lastly, we would like to say thanks to our classmates and to our family because all of them involve giving advices and giving strong supporting to us and also because of their praying, our job finished successful. We also want to take this opportunity to apologize if we had make mistake during this operation from the started until now. All the mistake came from us and all the kindness always come from Allah S.W.T